The The Effect of an Off-Feet Conditioning Protocol on Performance and Training Load Response to Intermittent Sprint Training Compared to an Equivalent Running Based Protocol - Timothy Rogers; Ryan Connell; Jarrod Free; Nicholas Gill; Kim Hebert-Losier; Martyn Beaven (International Journal of Strength and Conditioning)
Training for maximal intensity actions can lead to muscle damage, muscle soreness, and neuromuscular fatigue if not carefully managed.  Due to this potential impact, coaches sometimes look to off-feet conditioning (OFC) as an alternative.